Effectiveness of Integrative Laughter Therapy to Reduce Academic Stress among Undergraduate Nursing Students - Perveen, Shagufta; Bashir, Rabia; Khalid, Muniba (Journal of Development and Social Sciences, 2024)
This study assessed the effectiveness of laughter therapy sessions on academic stress among undergraduate nursing students. Nursing institutes’ environments are stressful, frequently hindering students’ educational outcomes, physical health, and psychological well-being. Counseling therapy techniques can minimize mental issues and increase student retention. A quasi-experimental design was employed. Counseling sessions were conducted for the students. A validated self-administered questionnaire was used to gather both pre- and post-intervention data. Twenty undergraduate nursing students in Abbottabad were enrolled. The mean age of participants was 21.76 +0.89 years. Analysis of the results after the intervention showed a statistically significant reduction in academic stress scores, showing the intervention’s effectiveness. The study’s results in the pre-intervention phase showed that females scored significantly higher on the academic stress scale. The findings of the study provided evidence that laughter therapy is effective in reducing academic stress in undergraduate nursing students.